Exploring AI integration in continuing pharmacy education: A survey of emerging institutional practice and initial guidance - Murry, Logan T.; Catledge, Kimberly; Holderly, Matthew; Travlos, Dimitra V.; Engle, Janet P. (Currents in pharmacy teaching and learning, 2026)
The rapid evolution of artificial intelligence (AI) is reshaping pharmacy continuing education (CE), offering innovative content generation and administrative efficiencies. However, concerns regarding content validity, ethical implications, and responsible use remain underexplored among CE providers. This study aimed to evaluate the perspectives, practices, and needs of Continuing Pharmacy Education (CPE) providers regarding AI integration. In 2023 and 2025, the Accreditation Council for Pharmacy Education (ACPE) administered a cross-sectional survey to all accredited CPE providers (n = 260 in 2023 and n = 262 in 2025). Questions assessed presence of AI policies, current applications, faculty/staff training, anticipated future uses, and organizational concerns. Quantitative data were analyzed using descriptive statistics; open-ended responses were analyzed using a general inductive approach. Response rates were 15 % (n = 39) in 2023 and 17.6 % (n = 46) in 2025. In 2023, only one provider (2.6 %) reported an AI policy; by 2025, 17 providers (37 %) had implemented one. Common AI applications included refining tone and wording, generating presentation titles/objectives, drafting assessment items, performing gap analyses, and suggesting conference themes. Few organizations offered formal AI training, a minority embedded guidance or disclosure protocols within speaker toolkits. Primary concerns centered on legality, liability, best practices, and content validity. Although adoption of AI policy is increasing among CPE providers, gaps persist in training, ethical guidance, and implementation support. ACPE has created guidance for CE/CPD organizations seeking to assess AI readiness, standardize usage guidelines, and integrate transparent AI strategies into instructional design, supporting ethical, effective AI integration in CE.